Influence of storm surge on tidal range energy. (1st March 2017) - Lewis, M.J.; Angeloudis, A.; Robins, P.E.; Evans, P.S.; Neill, S.P.
Abstract: The regular and predictable nature of the tide makes the generation of electricity with a tidal lagoon or barrage an attractive form of renewable energy, yet storm surges affect the total water-level. Here, we present the first assessment of the potential impact of storm surges on tidal-range power. Water-level data (2000–2012) at nine UK tide gauges, where tidal-range energy is suitable for development (e.g. Bristol Channel), was used to predict power. Storm surge affected annual resource estimates −5% to +3%, due to inter-annual variability, which is lower than other sources of uncertainty (e.g. lagoon design); therefore, annual resource estimation from astronomical tides alone appears sufficient. However, instantaneous power output was often significantly affected (Normalised Root Mean Squared Error: 3%–8%, Scatter Index: 15%–41%) and so a storm surge prediction system may be required for any future electricity generation scenario that includes large amounts of tidal-range generation. The storm surge influence to tidal-range power varied with the electricity generation strategy considered (flooding tide only, ebb-only or dual; both flood and ebb), but with some spatial and temporal variability. The flood-only strategy was most affected by storm surge, mostly likely because tide-surge interaction increases the chance of higher water-levels on the flooding tide. Highlights: Storm surge effect to tidal range power was investigated. Tide-only theoretical and technical annual resource assessment is sufficient. Storm surges do affect timing and magnitude of power generated. Tidal range energy flood-only generation strategy most affected by surges. Electricity forecast system may be necessary for tidal-range development.